الأدب المغربي بعيون مشرقية - بريدة، حنان (مركز فكر للدراسات والتطوير, 2021)
تأخر الأدب المغربي الحديث في النشأة والتطور عن نظيره المشرقي، وكان هذا التأخر تأخر يمن وبركة، لأنه بعد أن نهل من الأدب المشرقي وتشرب أسسه وخصائصه الفنية، استطاع أن يفرض نفسه بين الآداب، وأن يملأ الخزانات العربية والأوربية كذلك، غير أن هناك من يصف هذا الأدب بأنه أدب مغمور، وهذا يرجع بالأساس إلى أصحابه ممن عنوا بدراسة الأدب المشرقي وأهملوا دراسة أدبهم المغربي إما عن قصد أو عن غير قصد، مما جعل الأدباء المشارقة ينظرون إليه نظرة تعال، باعتبار أنهم أصحاب فضل وأن الأدب المغربي لم يستطع أن يتبوأ المكانة الرفيعة التي تبوأها الأدب المشرقي، ونحن لا يمكن أن ننكر فضل أشقائنا العرب في إغناء ثقافتنا المغربية، وتزويدها بكل مستجدات النهضة الفكرية العربية، ولكن في الوقت نفسه لا يجعلنا نقدس هذا الفضل دون إعادة الاعتبار لأدبنا المغربي. فعلى الرغم من إعجابي وحبي للأدب المشرقي إلا أنني أعتز بأدبي المغربي، وأرفض هذه السلطة الأبوية والتبعية الجائرة، لذلك ارتأيت أن واجبي الوطني يفرض علي لفت انتباه القراء إلى أدبنا المغربي والاعتزاز به، وإثبات علاقة التأثير والتأثر بين الأدب المغربي ونظيره المشرقي، إذ هي علاقة أخذ وعطاء وتلاقح وتناسج بدل علاقة تسلط وتمركز، لذلك اعتبرت مقالتي هاته بمثابة وسيلة لكشف اللثام عن بعض الأفكار الخاطئة في حق أدبنا المغربي والاعتزاز بكنوزنا الأدبية في المغرب.
Modern Moroccan literature lagged in its emergence and development from its eastern counterpart, and this delay was the delay of Yemen and its blessing, because after it drew from the Levantine literature and imbibed its foundations and artistic characteristics, it was able to impose itself between literature, and fill Arab and European tanks as well, but there are those who describe this Literature is an obscure literature, and this is mainly due to its companions who intended to study Levantine literature and neglected the study of their Moroccan literature either intentionally or unintentionally, which made the Levantine writers look to it in a glorious way, considering that they are the owners of virtue and that Moroccan literature has not been able to assume the high position that It has assumed oriental literature, and we cannot deny the merit of our Arab brothers in enriching our Moroccan culture and providing it with all the developments of the Arab intellectual renaissance, but at the same time it does not make us venerate this merit without re-regard for our Moroccan literature. Despite my admiration and love for Levantine literature, I cherish Moroccan literature, and I reject this patriarchal authority and unfair subordination, so I thought that my patriotic duty imposes on me to draw the readers ’attention to and pride in our Moroccan literature, and to prove the relationship of influence and influence between Moroccan literature and its eastern counterpart, as it is a relationship of taking And generosity, cross-fertilization, and harmony instead of a relationship of domination and concentration, so I considered my article this as a way to uncover some wrong ideas about the right of our Moroccan literature and pride in our literary treasures in Morocco.
Keywords: الأدب العربي -- الأدب المغربي -- التهميش الأدبي -- الأدباء المغاربة -- المغرب العربي